The history of lesbian literature: An exploration on the evolution of the genre - da Costa, Mariana Dias (Publishing Research Quarterly, 2022)
Cet article vise à examiner le développement de la littérature lesbienne à travers une discussion de son histoire. De la poésie grecque antique, où l'on découvre l'homonyme du terme lesbien et saphique, à la première moitié des années 1900 discutant des différent.e.s auteurices qui ont lutté contre la censure, en passant par les années 1950 pour explorer le genre qui a lancé la fiction lesbienne vers la popularité, et enfin abordant les œuvres modernes des dernières décennies. En examinant de manière critique les événements marquants qui ont façonné le paysage des œuvres à thème lesbien, nous pouvons comprendre l’effet profond que ces œuvres ont eu sur les lecteuricess et les écrivain.e.s.
Keywords: arts; discipline; genre; histoire et politique; personnes lesbiennes; ressource en ligne; thématiques; études littéraires

Lesbian potentiality and feminist media in the 1970s - Samer, Rox (Duke University Press, 2022)
In Lesbian Potentiality and Feminist Media in the 1970s, Rox Samer explores how 1970s feminists took up the figure of the lesbian in broad attempts to reimagine gender and sexuality. Samer turns to feminist film, video, and science fiction literature, offering a historiographical concept called “lesbian potentiality”—a way of thinking beyond what the lesbian was, in favor of how the lesbian signified what could have come to be. Samer shows how the labor of feminist media workers and fans put lesbian potentiality into movement. They see lesbian potentiality in feminist prison documentaries that theorize the prison industrial complex’s racialized and gendered violence and give image to Black feminist love politics and freedom dreaming. Lesbian potentiality also circulates through the alternative spaces created by feminist science fiction and fantasy fanzines like The Witch and the Chameleon and Janus. It was here that author James Tiptree, Jr./Alice B. Sheldon felt free to do gender differently and inspired many others to do so in turn. Throughout, Samer embraces the perpetual reimagination of “lesbian” and the lesbian’s former futures for the sake of continued, radical world-building.
Keywords: 1900-1999; 1970-1979; approches et analyses; arts; cinéma; communication; discipline; histoire et politique; lesbianisme; personnes lesbiennes; périodes historiques; ressource en ligne; thématiques; études littéraires